2010
DOI: 10.4319/lo.2010.55.2.0857
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of plankton‐derived dissolved organic matter in permeable coastal sediments

Abstract: We tested the hypothesis that dissolved organic carbon (DOC) is degraded when filtered through permeable shelf sediments. In a laboratory flume experiment the concave shape of DOC profiles observed in the upper 10 cm of Gulf of Mexico sublittoral sands was reproduced by the combination of DOC filtration and production in the sediment surface layer and mineralization and adsorption in the subsurface layer. Six percent to 14% of 13C‐labeled, highly degradable DOC was mineralized during filtration through 5.8‐cm‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 62 publications
2
25
0
Order By: Relevance
“…Here, we enlarge the geographical regions of P. brasiliensis to the north Atlantic coast and the kind of habit to the biofilm community of macroalgae. Typically, Planctomycetes appear in low percentage in natural populations, being more represented in marine sediments (Rusch et al, 2003;Musat et al, 2006;Chipman et al, 2010;Hu et al, 2010) when compared with coastal waters or also to the marine pelagic environment (Rusch et al, 2007). Even though we have not carried out any numerical study of the percentage of Planctomycetes in the macroalgae biofilm, the significant diversity encountered both in the number of isolates and in phylotypes indicates their ecological relevance.…”
Section: Planctomycetes Diversitymentioning
confidence: 96%
“…Here, we enlarge the geographical regions of P. brasiliensis to the north Atlantic coast and the kind of habit to the biofilm community of macroalgae. Typically, Planctomycetes appear in low percentage in natural populations, being more represented in marine sediments (Rusch et al, 2003;Musat et al, 2006;Chipman et al, 2010;Hu et al, 2010) when compared with coastal waters or also to the marine pelagic environment (Rusch et al, 2007). Even though we have not carried out any numerical study of the percentage of Planctomycetes in the macroalgae biofilm, the significant diversity encountered both in the number of isolates and in phylotypes indicates their ecological relevance.…”
Section: Planctomycetes Diversitymentioning
confidence: 96%
“…They have been found associated with micro-algae, seaweeds and detrital material (Morris et al, 2006;Longford et al, 2007;Bengtsson and Ovreås, 2010) where they are thought to be specialized degraders of sulphated polysaccharides produced by algae (Glöckner et al, 2003). It is likely that they perform a similar role within coastal sediments where they are also found in high abundance (Muscat et al, 2006;Chipman et al, 2010). Several moderately acidophilic Planctomycetes of the genera Schlesneria, Singulisphaera and Zavarzinella have been isolated from peat (Kulichevskaya et al, 2007;, but the diverse range of Planctomycetaceae found that only within cores receiving 3000 μatm CO 2 seawater could imply that the ability to take advantage of changing pH or CO2 conditions may be a feature of the family.…”
Section: Analysis Of 16s Rrna Amplicon Sequencesmentioning
confidence: 99%
“…Marine sands act as efficient biocatalytic filters that play an important role in the biogeochemical cycles of carbon and nutrients in shallow Gulf waters (11,19,20). Marine sands in the Gulf are covered with biofilms of highly diverse microbial communities (30,53), and the bacterial abundance in sands exceeds that of the overlying seawater by orders of magnitude (7,35,38).…”
mentioning
confidence: 99%